Abfraction lesions: etiology, diagnosis, and treatment options - Nascimento MM; Dilbone DA; Pereira PN; Duarte WR; Geraldeli S; Delgado AJ (Dove Medical Press, 2016)
Marcelle M Nascimento,1 Deborah A Dilbone,1 Patricia NR Pereira,1 Wagner R Duarte,2,3 Saulo Geraldeli,1 Alex J Delgado1 1Department of Restorative Dental Sciences, Division of Operative Dentistry, 2Department of Periodontology, College of Dentistry, University of Florida, Gainesville, FL, USA; 3Private Practice, Brasilia, DF, Brazil Abstract: Abfraction is a type of noncarious cervical lesion (NCCL) characterized by loss of tooth tissues with different clinical appearances. Evidence supports that abfraction lesions, as any NCCLs, have a multifactorial etiology. Particularly, the cervical wear of abfraction can occur as a result of normal and abnormal tooth function and may also be accompanied by pathological wear, such as abrasion and erosion. The interaction between chemical, biological, and behavioral factors is critical and helps to explain why some individuals exhibit more than one type of cervical wear mechanism than others. In an era of personalized dentistry, patient risk factors for NCCLs must be identified and addressed before any treatment is performed. Marked variations exist in dental practice concerning the diagnosis and management of these lesions. The lack of understanding about the prognosis of these lesions with or without intervention may be a major contributor to variations in dentists’ management decisions. This review focuses on the current knowledge and available treatment strategies for abfraction lesions. By recognizing that progressive changes in the cervical area of the tooth are part of a physiologically dynamic process that occurs with aging, premature and unnecessary intervention can be avoided. In cases of asymptomatic teeth, where tooth vitality and function are not compromised, abfraction lesions should be monitored for at least 6 months before any invasive procedure is planned. In cases of abfraction associated with gingival recession, a combined restorative-surgical approach may be performed. Restorative intervention and occlusal adjustment are not indicated as treatment options to prevent further tooth loss or progression of abfraction. The clinical decision to restore abfraction lesions may be based on the need to replace form and function or to relieve hypersensitivity of severely compromised teeth or for esthetic reasons. Keywords: abfraction, tooth wear, noncarious cervical lesions, tooth restoration